The Effect of Work Environment and Workload on Employee Job Satisfaction in the Operational Logistics Division of Pos Indonesia, Surabaya Main Branch - Mohamad Samsul Reza; Mei Retno Adiwati (International Forum of Researchers and Lecturers, 2025)
This research investigates the impact of the work environment and workload on job satisfaction among employees in the Operational Logistics Division at Pos Indonesia, Surabaya Main Branch. A quantitative method was applied with a total of 45 respondents selected through a saturated sampling technique. Data were obtained using interviews, questionnaires, and observations based on a Likert scale, and analyzed using Partial Least Square (PLS). The results reveal that the work environment has a positive and significant effect on job satisfaction, while workload has a negative and significant effect. These findings indicate that an improved work environment increases employee job satisfaction, whereas higher workloads tend to decrease it.